2005
DOI: 10.1111/j.1526-100x.2005.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Grassland Plants for Restoration after Spotted Knapweed Invasion

Abstract: Invasions of North American grasslands by Spotted knapweed (Centaurea maculosa Lam.) are mediated in part by Spotted knapweed root exudation of (±)-catechin, a potent phytotoxin. Residual soil (±)-catechin may interfere with reestablishment of native grassland species even after Spotted knapweed populations are controlled. Grassland species that are resistant to (±)-catechin may be more successful for restoration of areas infested by Spotted knapweed. We evaluated the (±)-catechin resistance of 23 grassland sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 31 publications
6
52
0
Order By: Relevance
“…This occurred within the last 30 days of the experiment. ( §)-Catechin aVects roots more than shoots (Perry et al 2005a), and perhaps root inhibition exacerbated the eVects of high temperatures and drying soils, resulting in unusually strong eVects of ( §)-catechin. On the other hand, perhaps high temperatures exacerbated the eVect of ( §)-catechin on relatively more water-stressed roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurred within the last 30 days of the experiment. ( §)-Catechin aVects roots more than shoots (Perry et al 2005a), and perhaps root inhibition exacerbated the eVects of high temperatures and drying soils, resulting in unusually strong eVects of ( §)-catechin. On the other hand, perhaps high temperatures exacerbated the eVect of ( §)-catechin on relatively more water-stressed roots.…”
Section: Discussionmentioning
confidence: 99%
“…The ( §) racemic form of catechin was initially reported to frequently occur at or above t1,000 g g ¡1 in soils Perry et al 2005a;Thelen et al 2005), but more detailed and extensive soil analyses have convincingly demonstrated that soil concentrations are much lower. Using a lower detection limit of 25 g g ¡1 , Perry et al (2007) found ( §)-catechin in less than 5% of C. maculosa rhizospheres, but at a site sampled repeatedly they recorded a pulse, in which ( §)-catechin was found in all 20 rhizospheres tested, of 650 § 450 (SD) g g ¡1 .…”
Section: Competition Experimentsmentioning
confidence: 98%
“…For example, lettuce may be unusually sensitive to some chemicals (Inderjit and Nilsen 2003) or unusually tolerant to others (Perry et al 2005a). This variation in response is likely to be true for all species and even among genotypes within a species (Callaway et al 2005a, b).…”
Section: Traditional Approachmentioning
confidence: 99%
“…Nakano et al (2001Nakano et al ( , 2003 isolated L-tryptophan from P. juliflora leaves, and implicated L-tryptophan leached from the foliage of P. juliflora as a potential allelochemical in Petri dish experiments, but again with species that do not naturally occur with P. juliflora. The selection of bioassay species is crucial to the study of allelopathy as the effect of biochemicals can vary dramatically among test species (Inderjit and Nilsen 2003;Perry et al 2005a;Inderjit 2006).…”
Section: Congeneric Comparisonsmentioning
confidence: 99%
“…Although species that are sensitive to the allelopathic effects of knapweed can persist in knapweed-infested areas (Perry et al 2005), very little research has been published detailing which native forbs are capable of establishing in the presence of knapweed. We observed native forb establishment in all treatments, including those that retained high knapweed cover (Table 2).…”
Section: Seeding Effectsmentioning
confidence: 99%